Pendampingan Himpunan Mahasiswa Program Studi Tadris Bahasa Indonesis dalam Pelaksanaan Safari Ramadan di SMAN 1 Muncar Banyuwangi: Pendampingan Himpunan Mahasiswa Program Studi Tadris Bahasa Indonesis dalam Pelaksanaan Safari Ramadan di SMAN 1 Muncar Banyuwangi - Manshur, Ali; Moh. Abdul QOhar; FINA ZAIDATUL ISTIQOMAH; Diyaana Hadad; Muhammad Bahrul Ulum; Luthfiyatun Nisa (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
The assistance of the Ramadan safari activity carried out by the HMPS Tadris Bahasa Indonesia UIMSYA Blokagung Banyuwangi is one form of implementation of the tridharma of higher education. This activity aims to provide students with provisions related to spiritual and social values. The method used in this activity is more focused on the implementation stage of the activity which includes three stages: the planning stage, implementation and evaluation. The results of this community service activity are in accordance with what is expected. This can be seen from the good response from SMAN 1 Muncar and students as participants in this activity. Mainly from the concept of the activity and the material that has been prepared and arranged for the smooth running of this year's Ramadan safari activity.